Preparation method for high-efficiency in-situ synthesis of (Ni2B + C) / Cu composite material

By performing densification and in-situ reaction separately, the problems of low preparation efficiency and difficult control of enhanced phase distribution in the prior art are solved, and efficient preparation of (Ni2B+C)/Cu composite materials with excellent performance are achieved.

CN119553124APending Publication Date: 2025-03-04XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938702.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The inefficient preparation of existing in-situ reaction preparation of metal-based composite materials and the mismatch of the sintering temperature and the in-situ reaction temperature lead to uncontrollable enhancement phase size and distribution.

Method used

The method of densifying and in-situ reaction of materials is used separately, and the pressure-free in-situ reaction sintering is performed first, and the degree of in-situ reaction is performed is controlled by finely adjusting the reaction temperature and time.

Benefits of technology

It improves the densification degree and preparation efficiency of composite materials, can effectively control the size and distribution of the enhanced phases, and improves the conductive and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553124A_ABST
    Figure CN119553124A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-efficiency in-situ synthesized (Ni2B + C) / Cu composite material, which comprises the following steps: weighing Cu-10wt.% Ni powder and B4C powder, and mixing to obtain a mixture C; the mixture C is placed in a graphite mold to be subjected to densification sintering with pressure in a vacuum environment, and after furnace cooling, a densified Cu-Ni-B4C block is obtained; and the densified Cu-Ni-B4C blocks are placed in a vacuum environment in batches to be subjected to non-pressure in-situ reaction sintering treatment, and the (Ni2B + C) / Cu composite material is obtained after furnace cooling. According to the method, the material is firstly subjected to densification sintering and then subjected to the in-situ reaction, under the condition that the density of the composite material is kept unchanged, the efficiency of preparing the copper-based composite material through the in-situ reaction is further improved, the energy consumption is reduced, the electric conductivity, the hardness, the tensile strength and the ductility of the copper-based composite material are improved, and therefore the copper-based composite material can be better applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite material manufacturing and powder metallurgy, and specifically relates to a high-efficiency in-situ synthesis (Ni 2 Preparation method of B+C) / Cu composite material. Background Art

[0002] With the rapid development of the industrial field, the requirements for the comprehensive performance of copper-based composites in this field are increasing day by day. Especially in key applications such as electrical contacts, high-speed railway systems, conductive rings and contact wires, copper-based composites must not only maintain their excellent conductive properties, but also have a certain strength. In order to improve the performance of copper-based composites, an effective strategy is to use in-situ generation technology to introduce ceramic phases or self-lubricating phases into the copper matrix. The interface between this in-situ generated reinforcement phase and the matrix is ​​pure and free of impurities, which can significantly improve the bonding performance of the two-phase interface in the material, thereby giving the material excellent thermodynamic stability. In Cu-Ni-B 4 In the C system, due to the in-situ generation of Ni in the copper matrix 2 The B reinforcement phase has high strength and good electrical conductivity, and the additional product C has good self-lubricating properties. Therefore, it is expected to prepare (Ni 2 B+C) / Cu composite materials.

[0003] At present, common powder metallurgy methods for copper-based composite materials include pressureless sintering and hot pressing sintering. The pressureless sintering method is favored for its simple equipment and easy industrial production, but the composite materials prepared by this method often have a low degree of densification, which affects the overall strength and integrity of the material; although the hot pressing sintering method can prepare highly densified composite materials, its preparation efficiency is low and it is generally suitable for laboratory scale rather than industrial batch production. In addition, for composite materials prepared by in-situ reaction, the material achieves densification and in-situ reaction simultaneously during the sintering process, but the suitable temperatures for the two are often different. In most cases, the sintering process parameters are formulated based on densification. Exceeding the in-situ reaction temperature of the system will cause excessive coarsening of the reinforcing phase, affecting the performance of the composite material. Therefore, it is necessary to develop a new preparation process to make the composite material highly densified while reducing the preparation cycle and energy consumption, and to accurately control the degree of in-situ reaction by finely adjusting the reaction temperature and time, which is a good way to prepare (Ni 2 The key to B+C) / Cu composite materials. Summary of the invention

[0004] The purpose of the present invention is to provide a high-efficiency in-situ synthesis (Ni 2The preparation method of B+C) / Cu composite material solves the problems of low preparation efficiency of existing in-situ reaction preparation of metal-based composite materials and uncontrollable reinforcement phase size and distribution due to mismatch between sintering temperature and in-situ reaction temperature during the preparation process.

[0005] The technical solution adopted by the present invention is to synthesize (Ni 2 The preparation method of the B+C) / Cu composite material is specifically implemented according to the following steps: Step 1: Weigh Cu-10wt.%Ni powder and B 4 C powder, add vacuum pump oil to Cu-10wt.%Ni powder and mix the two thoroughly to obtain mixture A; then add weighed B 4 C powder is subjected to ball milling and vibration mixing to obtain mixture C; Step 2: Place the mixture C obtained in step 1 in a graphite mold and perform pressure densification sintering in a vacuum environment. After cooling in the furnace, a densified Cu-Ni-B 4 C block; Step 3: densify the Cu-Ni-B obtained in step 2 4 C blocks are placed in a vacuum environment for pressureless in-situ reaction sintering, and after cooling in the furnace, (Ni 2 B+C) / Cu composite materials.

[0006] The present invention is also characterized in that: Step 1 is as follows: Step 1.1, weigh Cu-10wt.%Ni powder and B in a mass ratio of 85:0.9-1.1 respectively. 4 C powder, add vacuum pump oil to the weighed Cu-10wt.%Ni powder, and then mix the powder in a three-dimensional vibration powder mixer for 1-2 hours at a frequency of 40-60Hz to obtain a mixture A; Step 1.2: weigh the B 4 C powder is added to mixture A to obtain mixture B, and mixture B is mixed in a three-dimensional vibration mixer for 1-2 hours. ZrO is added during the mixing process. 2 Grinding ball, and ZrO 2 The mass ratio of the grinding balls to the mixture B is 1:1-3, the frequency of the powder mixer is 40-60 Hz, and the mixture C is obtained after powder mixing.

[0007] The particle size of Cu-10wt.%Ni powder is 100-150μm, B 4 The particle size of C powder is 0.5-1μm.

[0008] The mass of vacuum pump oil is 0.6wt.%-1wt.% of the mass of Cu-10wt.%Ni powder In step 1.2, a large ball ZrO 2 Grinding balls and small balls ZrO 2 Grinding balls are used to mix the powder, among which the large balls ZrO 2 The diameter of the grinding ball is 8-11mm, the small ball ZrO 2 The diameter of the grinding balls is 3-6 mm.

[0009] The densification sintering process of step 2 is specifically as follows: Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 30-40MPa, raise the furnace temperature to 850-950℃ within 60min and keep it for 0-30min for densification sintering, and then cool with the furnace.

[0010] The diameter of the graphite die is 40 mm.

[0011] The in-situ reaction sintering process in step 3 is: Densified Cu-Ni-B 4 C blocks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, raise the temperature in the furnace to 600℃-900℃ within 90min and react in situ for 5-120min, then cool with the furnace.

[0012] The beneficial effects of the present invention are: The method of the present invention separates the densification and in-situ reaction of the material, firstly performs the densification sintering with pressure, and then performs the in-situ reaction sintering treatment without pressure. After the green body is densified, the in-situ reaction can be carried out in batches, and the size and distribution of the reinforcing phase inside the green body can be effectively regulated, which solves the problem that the size and distribution of the reinforcing phase cannot be controlled due to the mismatch between the sintering temperature and the in-situ reaction temperature in the existing in-situ reaction process for preparing metal-based composite materials. The preparation process of the method of the present invention is simple, energy-saving, and at the same time (Ni 2 The B+C) / Cu composite material has high preparation efficiency, and the prepared composite material has excellent electrical conductivity and mechanical properties. In addition, the method of the present invention is suitable for preparing metal-based composite materials by various in-situ reactions, has a wide range of applications, and is extremely practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic flow diagram of the method of the present invention; Figure 2 The microstructure is 1000 times that of the sample obtained in Example 1 of the present invention; Figure 3 The microstructure is 1000 times that of the sample obtained in Example 2 of the present invention; Figure 4 The microstructure is 1000 times that of the sample obtained in Example 3 of the present invention; Figure 5 It is a 1000-fold microstructure of the sample obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0014] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0015] The invention provides high efficiency in-situ synthesis (Ni 2 Preparation method of B+C) / Cu composite material, such as Figure 1 As shown, the specific implementation steps are as follows: Step 1, powder mixing First, Cu-10wt.%Ni powder, B 4 The C powders were weighed in a mass ratio of 85:0.9-1.1; vacuum pump oil was then added to the weighed Cu-10wt.%Ni powder to prevent oxidation of the Cu-10wt.%Ni powder, with the mass of the added vacuum pump oil being 0.6wt.%-1wt.% of the mass of the Cu-10wt.%Ni powder; the powders were then mixed in a three-dimensional vibration powder mixer for 1-2h without adding grinding balls, and the frequency of the powder mixer was 40-60Hz to obtain a mixture A; the weighed B was then added to the mixture A; 4 C powder to obtain mixture B; the mixture B is mixed in a three-dimensional vibration mixer for 1-2 hours, and ZrO is added during the mixing. 2 Grinding ball, and ZrO 2 The mass ratio of the grinding balls to the mixture B is 1:1-3, the frequency of the powder mixer is 40-60 Hz, and the mixture C is obtained after powder mixing; Among them, the particle size of Cu-10wt.%Ni powder is 100-150μm, B 4 The particle size of C powder is 0.5-1μm. In the process of mixing the mixture B, large ball ZrO 2 Grinding balls and small balls ZrO 2 Grinding balls are used to mix the powder, among which the large balls ZrO 2 The diameter of the grinding ball is 8-11mm, the small ball ZrO 2 The diameter of the grinding balls is 3-6 mm.

[0016] Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold with a diameter of 40 mm and perform densification sintering in a vacuum environment: Place the mixture C in a graphite mold and put it into a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2Pa, set the furnace pressure to 30-40MPa, raise the furnace temperature to 850-950℃ within 60min and keep it at that temperature for 0-30min for densification sintering, and get the densified Cu-Ni-B with the furnace cooling. 4 C block.

[0017] Step 3: In-situ reaction sintering of the densified block The densified Cu-Ni-B prepared in step 2 4 C blocks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, raise the furnace temperature to 600℃-900℃ within 90min and react in situ for 5-120min, then cool down with the furnace. 2 The preparation of B+C) / Cu composite material is completed.

[0018] Example 1 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.84g Cu-10wt.% Ni powder and 1.16g B 4 C powder, wherein the particle size of Cu-10wt.%Ni powder is 150μm, B 4 The particle size of C powder is 0.5 μm; then, 0.8 wt.% vacuum pump oil is added to the weighed Cu-10 wt.% Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 1 hour to obtain a mixture A, and the frequency of the powder mixer is 50 Hz; then, the weighed B is added to the mixture A. 4 C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 1 hour, the ball-to-material mass ratio was 1:1, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2 The diameter of the grinding ball is 10 mm, and the small ball ZrO 2 The diameter of the grinding ball is 5 mm, the frequency of the powder mixer is 50 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 40MPa, raise the furnace temperature to 950℃ within 60min and keep it for 15min for densification sintering, and get the densified Cu-Ni-B with the furnace cooling. 4 C block.

[0019] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 600℃ within 90min and the reaction was carried out for 60min, and the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0020] The (Ni 2 The microstructure of B+C) / Cu composites is shown in Figure 2. Figure 2 As shown in the figure, it can be seen that at the in-situ reaction temperature of 600℃, a small amount of fine Ni 2 B reinforcement phase particles. Using Archimedes drainage method to measure (Ni 2 B+C) / Cu composite material density; using HBRV-187.5 electric Brinell hardness tester, test force 30kgf, holding time 30s, measured Vickers hardness; using Sigma2008b digital eddy current metal conductivity meter measured the conductivity of the composite material; prepared by the above method in this embodiment (Ni 2 The density, hardness and conductivity of the B+C) / Cu composite material were tested, and the density was found to be 8.8 g / cm 3 , hardness is 109.4HV, and conductivity is 26.3%IACS.

[0021] Example 2 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.84g Cu-10wt.% Ni powder and 1.16g B 4 C powder, wherein the particle size of Cu-10wt.%Ni powder is 150μm, B 4 The particle size of C powder is 0.5 μm; then 0.8 wt.% vacuum pump oil is added to the weighed Cu-10 wt.% Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 1 hour to obtain a mixture A, and the frequency of the powder mixer is 50 Hz; then weighed B is added to the mixture A 4 C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 1 hour, the ball-to-material mass ratio was 1:1, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2The diameter of the grinding ball is 10 mm, and the small ball ZrO 2 The diameter of the grinding ball is 5 mm, the frequency of the powder mixer is 50 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 40MPa, raise the furnace temperature to 950℃ within 60min and keep it for 15min for densification sintering, and get the densified Cu-Ni-B with the furnace cooling. 4 C block.

[0022] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 700℃ within 90min and the reaction was carried out for 60min, and then the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0023] The (Ni 2 The microstructure of B+C) / Cu composites is shown in Figure 2. Figure 3 As shown in the figure, it can be seen that at the in-situ reaction temperature of 700℃, the Ni 2 The size and area ratio of the B reinforcement phase particles are significantly increased compared with Example 1. 2 The density, hardness and conductivity of the B+C) / Cu composite material were tested, and the density was found to be 8.8 g / cm 3 , hardness is 115.2HV, and conductivity is 27.3%IACS.

[0024] Example 3 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.84g Cu-10wt.% Ni powder and 1.16g B 4 C powder, wherein the particle size of Cu-10wt.%Ni powder is 150μm, B 4 The particle size of C powder is 0.5 μm; then 0.8 wt.% vacuum pump oil is added to the weighed Cu-10 wt.% Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 1 hour to obtain a mixture A, and the frequency of the powder mixer is 50 Hz; then weighed B is added to the mixture A 4C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 1 hour, the ball-to-material mass ratio was 1:1, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2 The diameter of the grinding ball is 10 mm, and the small ball ZrO 2 The diameter of the grinding ball is 5 mm, the frequency of the powder mixer is 50 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 40MPa, raise the furnace temperature to 950℃ within 60min and keep it for 15min for densification sintering, and get the densified Cu-Ni-B with the furnace cooling. 4 C block.

[0025] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 800℃ within 90min and the reaction was carried out for 60min, and the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0026] The (Ni 2 The microstructure of B+C) / Cu composites is shown in Figure 2. Figure 4 As shown in the figure, it can be seen that at the in-situ reaction temperature of 800℃, the Ni inside the copper matrix 2 The size and area ratio of the B reinforcement phase particles are further increased. 2 The density, hardness and conductivity of the B+C) / Cu composite material were tested, and the density was found to be 8.8 g / cm 3 , hardness is 119.2HV, and conductivity is 29.3%IACS.

[0027] Example 4 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.84g Cu-10wt.% Ni powder and 1.16g B 4C powder, wherein the particle size of Cu-10wt.%Ni powder is 150μm, B 4 The particle size of C powder is 0.5 μm; then 0.8 wt.% vacuum pump oil is added to the weighed Cu-10 wt.% Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 1 hour to obtain a mixture A, and the frequency of the powder mixer is 50 Hz; then weighed B is added to the mixture A 4 C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 1 hour, the ball-to-material mass ratio was 1:1, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2 The diameter of the grinding ball is 10 mm, and the small ball ZrO 2 The diameter of the grinding ball is 5 mm, the frequency of the powder mixer is 50 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 40MPa, raise the furnace temperature to 950℃ within 60min and keep it for 15min for densification sintering, and get the densified Cu-Ni-B with the furnace cooling. 4 C block.

[0028] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 900℃ within 90min and the reaction was carried out for 60min, and then the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0029] The (Ni 2 The microstructure of B+C) / Cu composites is shown in Figure 2. Figure 5 As shown in the figure, it can be seen that at the in-situ reaction temperature of 900℃, the Ni inside the copper matrix 2 The size and area ratio of the B reinforcement phase particles are the largest. 2 The density, hardness and conductivity of the B+C) / Cu composite material were tested, and the density was found to be 8.8 g / cm 3 , hardness is 125.3HV, and conductivity is 31.0%IACS.

[0030] Example 5 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.95g Cu-10wt.% Ni powder and 1.05g B 4 C powder, wherein the particle size of Cu-10wt.%Ni powder is 150μm, B 4 The particle size of C powder is 0.8 μm; then 1.0 wt. % vacuum pump oil is added to the weighed Cu-10 wt. % Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 2 hours to obtain a mixture A, and the frequency of the powder mixer is 40 Hz; then weighed B is added to the mixture A 4 C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 1 hour, the ball-to-material mass ratio was 1:2, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2 The diameter of the grinding ball is 8mm, and the small ball ZrO 2 The diameter of the grinding ball is 5 mm, the frequency of the powder mixer is 60 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 30MPa, raise the furnace temperature to 850℃ within 60min and keep it for 30min for densification sintering, and get the densified Cu-Ni-B with furnace cooling. 4 C block.

[0031] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 800℃ within 90min and the reaction was carried out for 5 minutes, and the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0032] Example 6 This embodiment efficiently synthesizes (Ni 2 The preparation method of B+C) / Cu composite material comprises the following steps: Step 1, powder mixing Weigh 98.72g Cu-10wt.% Ni powder and 1.28g B4 C powder, wherein the particle size of Cu-10wt.%Ni powder is 120μm, B 4 The particle size of C powder is 1 μm; then 0.6 wt.% vacuum pump oil is added to the weighed Cu-10 wt.% Ni powder, and the powder is mixed in a three-dimensional vibration powder mixer for 1 hour to obtain a mixture A, and the frequency of the powder mixer is 60 Hz; then weighed B is added to the mixture A 4 C powder to obtain mixture B; the mixture B was mixed in a three-dimensional vibration mixer for 2 hours, the ball-to-material mass ratio was 1:3, and the grinding balls used for mixing were ZrO 2 Grinding balls, grinding balls are made of large balls of ZrO 2 Grinding balls and small balls ZrO 2 Grinding ball composition, large ball ZrO 2 The diameter of the grinding ball is 11mm, and the small ball ZrO 2 The diameter of the grinding ball is 3 mm, the frequency of the powder mixer is 40 Hz, and the mixture C is obtained after mixing the powder; Step 2: Sintering of mixed powder for densification Place the mixture C obtained in step 1 in a graphite mold and place it in a vacuum rapid hot pressing sintering furnace, and set the vacuum degree in the furnace to less than 10 -2 Pa, set the furnace pressure to 35MPa, raise the furnace temperature to 950℃ within 60min and keep it for 5min for densification sintering, and get the densified Cu-Ni-B with furnace cooling. 4 C block.

[0033] Step 3: In-situ reaction sintering of the densified block First, the densified Cu-Ni-B prepared in step 2 4 C blanks are put into a vacuum box furnace in batches, and the vacuum degree in the furnace is set to less than 10 -2 Pa, the furnace temperature was raised to 600℃ within 90min and the reaction was carried out for 120min, and then the furnace was cooled. 2 The preparation of B+C) / Cu composite material is completed.

[0034] Comparative Example 1 This comparative example is substantially the same as Example 4, except that step 3 is not performed.

[0035] Comparative Example 2 In this comparative example, the densification and in-situ reaction of the material are carried out simultaneously, which is basically the same as Example 4, except that the densification sintering time in step 2 is 60 minutes and step 3 is not performed.

[0036] The density, hardness, conductivity, tensile strength and elongation of the composite materials prepared in Example 4, Comparative Example 1 and Comparative Example 2 were tested, and the test results are shown in Table 1 below: Table 1 Material performance test results

[0037] As can be seen from Table 1, by comparing Comparative Example 1 and Comparative Example 2, as the densification time increases, the density of the sample does not change, the hardness decreases, but the conductivity, tensile strength and elongation increase. Compared with Comparative Example 2, which was directly sintered for 60 minutes, the hardness, conductivity, tensile strength and elongation of the composite material prepared by Example 4 using the strategy of "densification first, then in-situ reaction" are significantly improved, which shows that the method of the present invention is effective for in-situ synthesis (Ni 2 The preparation efficiency of B+C) / Cu composite materials has been significantly improved, and the performance has been significantly improved.

Claims

1. A method for preparing a high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material, characterized in that: Follow the steps below to implement it: Step 1, weighing Cu-10wt.% Ni powder and B4C powder, adding vacuum pump oil to the Cu-10wt.% Ni powder and mixing the two thoroughly to obtain a mixture A; then adding the weighed B4C powder to the mixture A, and mixing the powders by ball milling and vibration to obtain a mixture C; Step 2, placing the mixture C obtained in step 1 in a graphite mold and performing pressure densification sintering in a vacuum environment, and cooling in the furnace to obtain a densified Cu-Ni-B4C block; Step 3: Place the densified Cu-Ni-B4C blocks obtained in step 2 in batches in a vacuum environment for pressureless in-situ reaction sintering treatment, and after cooling in the furnace, obtain a (Ni2B+C) / Cu composite material.

2. The method for preparing the high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1, characterized in that: Step 1 is as follows: Step 1.1, according to the mass ratio of 85: Cu-10wt.% Ni powder and B4C powder were weighed in a ratio of 0.9-1.1, vacuum pump oil was added to the weighed Cu-10wt.% Ni powder, and then the powders were mixed in a three-dimensional vibration powder mixer for 1-2 hours at a frequency of 40-60 Hz to obtain a mixture A; Step 1.2, add the B4C powder weighed in step 1.1 to mixture A to obtain mixture B, mix mixture B in a three-dimensional vibration mixer for 1-2 hours, add ZrO2 grinding balls during mixing, and the mass ratio of ZrO2 grinding balls to mixture B is 1:1-3, the frequency of the mixer is 40-60 Hz, and mixture C is obtained after mixing.

3. The method for preparing a high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1 or 2, characterized in that: The particle size of the Cu-10wt.%Ni powder is 100-150 μm, and the particle size of the B4C powder is 0.5-1 μm.

4. The method for preparing a high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1 or 2, characterized in that: The mass of the vacuum pump oil is 0.6wt.%-1wt.% of the mass of the Cu-10wt.%Ni powder.

5. The method for preparing the high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 2, characterized in that: In step 1.2, large ZrO2 grinding balls and small ZrO2 grinding balls are used for powder mixing, wherein the diameter of the large ZrO2 grinding balls is 8-11 mm, and the diameter of the small ZrO2 grinding balls is 3-6 mm.

6. The method for preparing the high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1, characterized in that: The densification sintering process of step 2 is specifically as follows: Mixture C is placed in a graphite mold and placed in a vacuum rapid hot pressing sintering furnace. The vacuum degree in the furnace is set to less than 10 -2 Pa, set the furnace pressure to 30-40MPa, raise the furnace temperature to 850-950℃ within 60min and keep it for 0-30min for densification sintering, and then cool with the furnace.

7. The method for preparing the high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1, characterized in that: The diameter of the graphite mold is 40 mm.

8. The method for preparing the high-efficiency in-situ synthesized (Ni2B+C) / Cu composite material according to claim 1, characterized in that: The in-situ reaction sintering process in step 3 is: The densified Cu-Ni-B4C blocks were put into a vacuum box furnace in batches and the vacuum degree in the furnace was set to less than 10 -2 Pa, raise the temperature in the furnace to 600℃-900℃ within 90min and react in situ for 5-120min, then cool with the furnace.